Rethinking the Consultation-Conflict Link: Lessons from Bolivia's Gas Sector - Almut Schilling-Vacaflor (German Institute of Global and Area Studies (GIGA), 2013)
This article sheds light on 26 consultations in Bolivia's gas sector (2007-2012) and challenges simplified conceptions of prior consultation as a tool for conflict prevention and resolution. It shows that consultations do not only appease conflicts, but also exacerbate them as these procedures are used to negotiate broader grievances. This study further argues that narrow consultations (like those carried out in Bolivia) - rather than comprehensive ones - repress conflicts in the short-term by limiting opportunities to mobilize against extractive projects. It also reveals that the degree of conflict and prevention potential of consultations varied according to the affected groups and highlights the ambiguous effects of the entanglement of consultations and compensations.
Keywords: 300; prior consultation; FPIC; indigenous rights; extractive industry; resource conflicts; Bolivia